Ti4+ and Sn4+-bearing tourmalines - pressure control and comparison of synthetic and natural counterparts - Vereshchagin,O.S.; Wunder,B.; Baksheev,I.A.; Wilke,F.D.H.; Vlasenko,N.S.; Frank-Kamenetskaya,O.V. (Journal of Geosciences, 2022)
Me4+-bearing (Me4+ = Sn, Ti) dravite analogs were synthesized in the system MeO2-MgO-Al2O3-B2O3-SiO2-NaO-H2O at 700 °C and 4 / 0.2 GPa in four hydrothermal experiments. Tourmalines form rosette-like aggregates and needle-like crystals that are chemically homogeneous. Tourmaline crystals obtained in high-pressure runs (4 GPa) are much smaller (up to 0.1 × 2 μm) and have lower Me4+ (0.27 wt. % SnO2, 0.57 wt. % TiO2) than those from the low-pressure (0.2 GPa) runs (up to 1 × 5 μm; 1.77 wt. % SnO2, 2.25 wt. % TiO2). Synthetic analogs of rutile, quartz and coesite were obtained in the system TiO2-MgO-Al2O3-B2O3-SiO2-NaO-H2O, whereas synthetic analogs of cassiterite, tin-rich (up to ˜19.55 wt. % SnO2) Na-pyroxene, MgSn(BO3)2 (Mg-analogue of tusionite), quartz and coesite were synthesized in the system SnO2-MgO-Al2O3-B2O3-SiO2-NaO-H2O. We suggest that at a high temperature (≤ 700 °C), the pressure negatively affects the Ti incorporation into the tourmaline structure. In contrast, at relatively low pressures, the Ti incorporation in tourmaline structures is governed by the Ti content in the mineral-forming medium. Low-pressure conditions are feasible for Sn incorporation in the tourmaline structure. The presence of Ti4+ and Sn4+ cations in structures of the synthesized tourmalines (probably at octahedrally coordinated sites), is also indicated by changes in the unit-cell parameters.
Keywords: tourmaline; pyroxene; jadeite; tin; titanium; hydrothermal synthesis